Resistance and resilience of soil fluorescein diacetate activity against abiotic stress - VISHWANATH, VISHWANATH; KUMAR, SARVENDRA; PURAKAYASTHA, T J; DATTA, S P; G, ROSIN K; MAHAPATRA, P; SINHA, S K (The Indian Journal of Agricultural Sciences, 2021)
Present study was under taken to evaluate the impact of long-term application of fertilizers and lime on fluorescein diacetate (FDA) activity, and their resistance and resilience against heat stress (48°C for 24 h) in acidic Alfisol. To accomplish this, soil samples (0-15 cm depth) were collected from seven treatments (control, 100% N, 100% NP, 100% NPK, 100% NPK+ handweeding, 100% NPK+FYM and 100% NPK+lime) from soybean crop under long-term fertiliser experiment (LTFE) at Birsa Agricultural University, Ranchi (2018). Resistance and resilience capacity of FDA were analyzed at 1, 15, 30 and 60 days after heat stress (DAS). FDA in soil was significantly higher in NPK+FYM (747 Î¼g fluorescein g/soil/h) followed by100% NPK+hand weeding, 100% NPK+lime, 100% NPK, 100% NP, 100% N and control treatment. At 1 DAS, maximum reduction (69%) of FDA was noticed under 100% NP alone plots followed by 100% N (64%) treatments over initial value. Treatment 100% NPK+FYM had highest resistance index (0.33) with lowest resistance (0.19) was noticed in 100% NP alone treatment. Recovery rate of most of the treatments was higher during 15 to 30 DAS and almost 100 % recovery at 60 DAS. In nutshell, FDA emerged as a good indicator to assess resistance, resilience and functional behavior of soil against abiotic stress.